The Effect of Accountability and Digital Payment Literacy on Muzakki's Decision to Pay ZIS Online (Case Study of Baznas Probolinggo Regency) - Sholeha, Imroatus; Roifah, Tri Nadhirotur; Rahman, Moh Abd (Jurnal Iqtisaduna, 2025)
The influence of accountability and digital payment literacy on the decision of muzakki to pay ZIS online (case study of Baznas Probolinggo Regency). To analyze the influence of Baznas Probolinggo Regency’s accountability on the decision of muzakki to pay ZIS online. To examine the influence of muzakki's digital payment literacy on the decision to pay ZIS online, and to determine the simultaneous influence of accountability and digital payment literacy on the decision to pay ZIS online. In this study, the author uses a causal associative approach. The causal associative approach is used to determine the cause-and-effect relationship (causality) between two or more variables. Baznas Probolinggo Regency accountability influences the decision of muzakki to pay ZIS online, digital payment literacy influences the decision of muzakki to pay ZIS online.